When all else fails the ethics of resistance to state injustice - Brennan, Jason, 1979- (Princeton University Press, 2019)
The economist Albert O. Hirschman famously argued that citizens of democracies have only three possible responses to injustice or wrongdoing by their government: we may leave, complain, or comply. But in When All Else Fails, Jason Brennan argues that there is fourth option. When governments violate our rights, we may resist. We may even have a moral duty to do so. For centuries, almost everyone has believed that we must allow the government and its representatives to act without interference, no matter how they behave. We may complain, protest, sue, or vote officials out, but we can't fight back. But Brennan makes the case that we have no duty to allow the state or its agents to commit injustice. We have every right to react with acts of "uncivil disobedience." We may resist arrest for violation of unjust laws. We may disobey orders, sabotage government property, or reveal classified information. We may deceive ignorant, irrational, or malicious voters. We may even use force in self-defense or to defend others. The result is a provocative challenge to long-held beliefs about how citizens may respond when government officials behave unjustly or abuse their power.